2011
DOI: 10.1002/etc.684
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury and selenium speciation in different tissues of beluga whales (Delphinapterus leucas) from the western Canadian Arctic

Abstract: Monitoring data have shown that the total monomethylmercury (CH(3) Hg(+) and its complexes; collectively referred as MeHg hereafter) concentrations in Arctic marine mammals have remained very high in recent decades. Toward a better understanding of the metabolic and toxicological implications of these high levels of MeHg, we report here on the molecular forms of MeHg in the muscle, brain, liver, and kidneys of 10 beluga whales from the western Canadian Arctic. In all tissues analyzed, monomethylmercury was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 34 publications
4
26
1
Order By: Relevance
“…Similar THg values (0.13± 0.03 μg/g ww) were found in the brain tissue of six harp seal (Phoca groenlandica) pups collected from the Grise Fjord and Pangnirtung region of Nunavut (Ronald et al, 1984). Canadian beluga exhibited brain concentrations that are an order of magnitude greater than those in polar bears and seals (Lemes et al, 2011).…”
Section: Mercury-selenium Relationships and Interactionssupporting
confidence: 62%
See 1 more Smart Citation
“…Similar THg values (0.13± 0.03 μg/g ww) were found in the brain tissue of six harp seal (Phoca groenlandica) pups collected from the Grise Fjord and Pangnirtung region of Nunavut (Ronald et al, 1984). Canadian beluga exhibited brain concentrations that are an order of magnitude greater than those in polar bears and seals (Lemes et al, 2011).…”
Section: Mercury-selenium Relationships and Interactionssupporting
confidence: 62%
“…Other species having less fur, such as seals and walruses, and in toothed whales (beluga, narwhal, pilot whale), this excretion route is non-existent. Toothed whales are thus more at risk from Hg, and this is also reflected in their higher concentrations in brain, liver and muscle (Olsen et al, 2003;Dam, 2005, 2009;Sonne et al, 2010;Lemes et al, 2011).…”
Section: Comparison Of Polar Bear Hair Concentrations With Effect Guimentioning
confidence: 99%
“…Although previous research suggested that Se may detoxify MeHg in brain tissue of EBS beluga (Lemes et al 2011), our results suggest that Se is not fully protecting beluga from changes to the cholinergic and dopaminergic signaling pathways associated with MeHg exposure. In addition, previous research indicated that THg, MeHg, and Se were associated with variation in γ-amminobutyric acid type A receptor binding levels, and THg, iHg labile , and MeHg were associated with the expression of mRNA for GABA A -R subunit α2 in EBS beluga (Ostertag et al 2014).…”
Section: Discussioncontrasting
confidence: 99%
“…As the molar ratio of THg to Se approached 1, MAO activity decreased and mAChR binding levels increased. This can be explained by the potential protective effect of Se in the brain; previous analyses of brain tissue from EBS beluga identified a HgSe complex, which was hypothesized to contribute to demethylation and detoxification of MeHg in beluga organs (Lemes et al 2011). Our findings support the hypothesis that Se may detoxify MeHg.…”
Section: Mercury and Seleniumsupporting
confidence: 84%
See 1 more Smart Citation